Peranan Biaya Sosial dalam Meningkatkan Kinerja Sosial dan Kinerja Keuangan Perusahaan High Profile dan Low Profile - Hendarti, Henny (Journal the Winners: Economics, Business, Management, and Information System Journal, 2006)
Corporate social report had been done on company annual report in Indonesia. Workers theme was the most interesting theme amongs others. The condition happened consistently on high-profile dan low-profile industrial groups. But, corporate social report in Indonesia was still low. It was assumed because the company did not taking advantage to the annual report as a communication media between company and stakeholders. Possibly, it was because the company only used annual report as a report for the stakeholders and debt holders or as information for future investors. Another factor causing the low number was because the company was only done small social activities.